Main biopsychic factors related to the dental prosthetics rehabilitation in institutionalized elderly - Marcia Hortencia Corona Carpio; Eliannis Suárez Calzado; Maylin Lianza Rodríguez; Ana Buenaventura Duharte Escalante; Ibis Piña Odio (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Aging constitutes the most important demographic transformation nowadays. The higher proportion of elderly in the community supposes a challenge of extraordinary transcendence as for the satisfaction of their social, sanitary, economic and cultural demands. Objective: To determine the biopsychic factors related to the dental prosthetics rehabilitation in elderly.  Methods: A descriptive and cross-sectional study of 60 elderly was carried out in "Corazones contentos" Home for the elderly at Sueño neighborhood -categorized in adapted and resistant according to psychological factors- who went to the Prosthesis Department of Mártires del Moncada Teaching Provincial Stomatological Clinic in Santiago de Cuba, from March, 2018 to January, 2020. Results: In the series there was prevalence of 80 years and over patients from the female sex. As outstanding biological characteristic there is the total dental loss and as chronic non transmissible disease the diabetes mellitus was more frequent. In a same way, the higher number of elderly corresponded to the psychological category of resistant. Conclusions: Most of the elderly are characterized by a resistant psychological profile, determined by a style of passive confrontation, negative emotional expression and lack of autonomy, what conditioned a harmful attitude toward their oral health.